The recording engineer's handbook - Owsinski, Bobby; Gale Group (Boston, Mass. Artist Pro Publishing Boston, Mass. Thomson Course Technology PTR, 2005)
Everything you always wanted to know about tracking in stereo and surround, including advice from Grammy winning engineers. Includes sections on the history of classic microphones, condenser mic fallacies and getting the most from a vocalist, plus secrets of mic placement and choosing the right mic. There's also several different miking techniques for just about every instrument.
Preface -- Part 1: Tracking in stereo -- Part 2: Tracking in surround -- Part 3: The interviews -- Glossary -- Index.
Electronic reproduction.
Keywords: Sound -- Recording and reproducing -- Handbooks, manuals, etc; Sound recordings -- Production and direction -- Handbooks, manuals, etc; Music trade -- Handbooks, manuals, etc; Sound studios -- Handbooks, manuals, etc; Electronic books